2009
DOI: 10.1194/jlr.m900116-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibroblast mitochondrial 27-hydroxycholesterol production by active plasma membrane cholesterol

Abstract: This study addresses the regulation of the biosynthesis of oxysterol signal molecules. Side chain oxysterols such as 24-, 25-, and 27-hydroxycholesterol (HC) are derived from cholesterol in the endoplasmic reticulum (ER) and mitochondria and trigger downregulation of the abundance of cell cholesterol through diverse pathways ( 1-4 ). In particular, the association of oxysterols with nuclear liver X receptors (LXR) promotes the expression of ATP-binding cassette (ABC) transport proteins that transfer excess cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 47 publications
5
73
0
Order By: Relevance
“…ABCA3 has previously been shown to be involved in early steps of late endosomal biogenesis ( 15 ), and both MLN64 and ABCA3 have higher expression in lung where ABCA3 has been shown to be important for the secretion of late endosomal lipids at the PM. Cholesterol destined for the mitochondria passes through the PM ( 36 ). MLN64 is involved in the egress of cholesterol from LE to mitochondria ( 4 ) in a process that is independent of NPC1 ( 7 ), indicating that MLN64 may be involved in the traffi cking of cholesterol upstream of NPC1-and ORP1L-containing late endosomes as an additional step for LE cholesterol export.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA3 has previously been shown to be involved in early steps of late endosomal biogenesis ( 15 ), and both MLN64 and ABCA3 have higher expression in lung where ABCA3 has been shown to be important for the secretion of late endosomal lipids at the PM. Cholesterol destined for the mitochondria passes through the PM ( 36 ). MLN64 is involved in the egress of cholesterol from LE to mitochondria ( 4 ) in a process that is independent of NPC1 ( 7 ), indicating that MLN64 may be involved in the traffi cking of cholesterol upstream of NPC1-and ORP1L-containing late endosomes as an additional step for LE cholesterol export.…”
Section: Discussionmentioning
confidence: 99%
“…5A). We employed a concentration of U18666A (4.5 M) that has previously been shown to inhibit 27-hydroxycholesterol formation in the mitochondria and to increase HMGCR activity in the ER (38). It is also noteworthy that reducing cell cholesterol further by cyclodextrin treatment did not increase SREBP-2 target gene expression (as was also seen in the CD control in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Lange et al (38) have shown that following cholesterol enrichment with a deuterated cholesterol probe, the endogenous cholesterol is internalized prior to the exogenously loaded cholesterol complexed to cyclodextrin. Therefore, it might be argued that ACAT would first have been presented with endogenous cholesterol and raises the question of why this esterification was not detected with ent-cholesterol in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a permanently activated Er may well be the consequence of an association with endogenously produced SErms, such as 27Ohc. through the metabolism of profusely available plasma membrane cholesterol, many cells produce and secrete 27Ohc in their neighborhood, as demonstrated in the case of fibroblasts (28). The infiltration of macrophages is an indicator of poor prognosis in patients with a mammary gland affected by a tumor (29).…”
Section: Discussionmentioning
confidence: 99%